Effectiveness of guidance and counselling in promoting learners’ academic success in rural secondary schools, Vhembe district - Muluvhu Khathutshelo (International Journal of Studies in Inclusive Education)
Guidance and counselling is an enterprise that promotes learners’ performance globally and internationally. However, its effectiveness is not given enough attention since learners continue performing poorly in South Africa. This study investigates the effectiveness of guidance and counselling as an enterprise for promoting learner performance in rural secondary schools of Limpopo province. It used a qualitative approach. Twelve participants were purposively selected, such as ten educators’ guidance who were interviewed telephonically. The results showed that life orientation teachers agreed that guidance and counselling are an enterprise that promotes learners’ performance. It concluded that if guidance and counselling are implemented effectively, learners' performance in rural areas will improve. The study recommends that the Department of Education should promote the implementation of guidance and counselling by reviewing areas of guidance and counselling that need to be strengthened in rural areas.